Association of Sleep Characteristics With Nocturnal Hypertension and Nondipping Blood Pressure in the CARDIA Study. Issue 7 (9th April 2020) - Thomas, S. Justin; Booth, John N.; Jaeger, Byron C.; Hubbard, Demetria; Sakhuja, Swati; Abdalla, Marwah; Lloyd‐Jones, Donald M.; Buysse, Daniel J.; Lewis, Core E.; Shikany, James M.; Schwartz, Joseph E.; Shimbo, Daichi; et al.
Abstract : Background: Sleep characteristics and disorders are associated with higher blood pressure (BP) when measured in the clinic setting. Methods and Results: We tested whether self‐reported sleep characteristics and likelihood of obstructive sleep apnea (OSA) were associated with nocturnal hypertension and nondipping systolic BP (SBP) among participants in the CARDIA (Coronary Artery Risk Development in Young Adults) study who completed 24‐hour ambulatory BP monitoring during the year 30 examination. Likelihood of OSA was determined using the STOP‐Bang questionnaire. Global sleep quality, habitual sleep duration, sleep efficiency, and midsleep time were obtained from the Pittsburgh Sleep Quality Index. Nocturnal hypertension was defined as mean asleep SBP ≥120 mm Hg or diastolic BP ≥70 mm Hg. Nondipping SBP was defined as a decline in awake‐to‐asleep SBP <10%. Among 702 participants, the prevalence of nocturnal hypertension and nondipping SBP was 41.3% and 32.5%, respectively. After multivariable adjustment including cardiovascular risk factors, the prevalence ratios (PRs) for nocturnal hypertension and nondipping SBP associated with high versus low likelihood of OSA were 1.32 (95% CI, 1.00–1.75) and 1.31 (95% CI, 1.02–1.68), respectively. The association between likelihood of OSA and nocturnal hypertension was stronger for white participants (PR: 2.09; 95% CI, 1.23–3.48) compared with black participants (PR: 1.11; 95% CI, 0.79–1.56). The PR for nondipping SBP associated with a 1‐hour later midsleep time was 0.92 (95% CI, 0.85–0.99). Global sleep quality, habitual sleep duration, and sleep efficiency were not associated with either nocturnal hypertension or nondipping SBP. Conclusions: These findings suggest that addressing OSA risk and sleep timing in a clinical trial may improve BP during sleep.